Energy expenditure during constant and variable intensity cycling: Validty of power based estimates - Haakonssen, E.; Martin, D.; Burke, L.; Jenkins, D. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Accurate estimates of exercise energy expenditure (EE) influence energy intake recommendations for elite athletes. Commercially available power meters (i.e., SRM Julich, Germany) are used to quantify training load and estimate cycling EE. The aim of this study was to measure gross efficiency (GE) during constant and variable intensity cycling to evaluate the accuracy of estimating EE with power meters. Methods: Nine national team female cyclists (mean±stdev; 24.2±3.1 yrs, 57.7±5.1 kg, 64.2±4.0 ml/kg/min VO2pk, 287±23 W Maximum Aerobic Power (MAP)) were recruited. Cyclists completed a gross efficiency test (GEtest = 4 min at ~45%, ~55%, ~65% and ~75% MAP) followed by 10.5 min of either constant or variable intensity cycling averaging ~55% MAP and then completed a second GEtest. The variable power trial involved 1 min @ 45% MAP and 30sec @ 75% MAP repeated 7 times. Testing was performed on a high kinetic energy, wind-braked cycle ergometer instrumented with a SRM PowerMeter (Science Version, 8sg). Cadence was self selected. Expired gases were analysed by open circuit, indirect calorimetry using a custom built automated Douglas Bag system. During GEtests, Economy (W.L-1), VO2 at 150 W (VO2@150W) and average Gross Efficiency (GE) were calculated. EE (kJ) for 1hr of constant and variable cycling was estimated using indirect calorimetry and compared to predicted EE based on power (SRM) and GE estimated for the group and for the individual. Results: Typical error (Mean±90% CI) calculated from pre-GEtests log-transformed data reflect reliable measurements of Economy - 7.0±6.0%; VO2@150W - 2.4±2.1%; and GE - 2.1±1.8%. Individual GE ranged from 16.0-21.2%. Following constant and variable intensity cycling, there were small but consistent changes in Economy (~3-8%), GE (~-2%) and VO2@150w (~3%). GE during constant (18.4±1.6%) and variable intensity cycling (18.6±1.1%) was similar. SRM based estimates of EE for 1hr of cycling using the average GE (18.5%) were within ~30 kJ (<1%) of EE estimated from indirect calorimetry. However, individual errors ranged from -15% to 14%. Using each individual`s GE produced estimates of EE within ~10 kJ (<0.4%, range:-1% to 4%). Discussion: The gross efficiency (GE) of cycling for national team female cyclists was ~19%. GE was similar for ~10 min of constant and variable intensity cycling. Findings support the use of calibrated SRM power meters for estimating cycling EE. For trained, competitive female road cyclists, total mechanical work (kJ) multiplied by 5.3 provides a valid estimation of total EE during constant and variable cycling <75% VO2pk. Combining SRM power meter data with each cyclist`s individually assessed GE greatly improves the accuracy of estimates for EE (<4% error in all cases).